1993
DOI: 10.1136/sti.69.4.251
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence and risk behaviour among prostitutes and clients in Amsterdam: migrants at increased risk for HIV infection.

Abstract: Objectives-To study groups of prostitutes and clients of prostitutes in order (i) to determine HIV prevalence and sexual risk behaviour, (ii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In just under half of European-based studies, the prevalence of HIV was less than 1.5% among migrants and non-migrants alike 29 30 33 36. In all these studies, the prevalence of injecting drug use was low.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In just under half of European-based studies, the prevalence of HIV was less than 1.5% among migrants and non-migrants alike 29 30 33 36. In all these studies, the prevalence of injecting drug use was low.…”
Section: Resultsmentioning
confidence: 98%
“…The remaining 13 studies focussed on international or intracontinental migration moving from low-income or middle-income to high-income countries. Destination countries included Australia,23 37 Spain,29 30 Portugal,31 Italy,34 35 the Netherlands,36 UK,33 Hong Kong42 43 and Turkey 28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This also corroborates the results obtained from local studies conducted on clients of FSW Lau, Tsui, & Ho, 2005), showing similar differentials by locales. As migrant sex workers and commercial sex activities among travelers have been common (Hawkes et al, 1994;Matteelli et al, 2003;van Haastrecht et al, 1993), the observed geographic differentials in condom use among FSW and/or their clients may also occur in other places. To our knowledge, this is the first study of this type.…”
Section: Discussionmentioning
confidence: 99%